2020
DOI: 10.1111/1440-1681.13221
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin attenuates altered redox homeostasis in an experimental hyperlipidaemic model of rat

Abstract: Diets rich in saturated fats and cholesterol contribute to the incidence of hyperlipidaemia. An altered lipid profile is a major factor responsible for the development of CVD. Male Wistar rats were fed with a high‐fat diet (HFD) (suspension (w/v) of 0.5% cholesterol, 3% coconut oil and 0.25% cholic acid for 30 days) to induce an experimental hyperlipidaemic model. High‐fat diet fed rats were also supplemented with hesperidin (100 mg/kg body weight). The present study reports reactive oxygen species (ROS) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…In this case, hesperidin did not play a significant preventive effect. This agrees with a study reporting that daily hesperidin supplementation (100 mg/kg BW) did not restore the higher IL-6 secretion induced by high-fat diet intake in Wistar rats [44]. Nevertheless, other studies show that crude polyphenols extracted from blossoms of Citrus aurantium L. var.…”
Section: Discussionsupporting
confidence: 91%
“…In this case, hesperidin did not play a significant preventive effect. This agrees with a study reporting that daily hesperidin supplementation (100 mg/kg BW) did not restore the higher IL-6 secretion induced by high-fat diet intake in Wistar rats [44]. Nevertheless, other studies show that crude polyphenols extracted from blossoms of Citrus aurantium L. var.…”
Section: Discussionsupporting
confidence: 91%
“…This bioflavonoid exhibits antioxidant, anti-inflammatory, and antibacterial effects [ 14 , 15 ]. A recent study has demonstrated that hesperidin protected cells against redox imbalances [ 16 ]. In addition, hesperidin markedly reduces oxidative stress-induced inflammatory cytokine levels and apoptosis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once isolated EVs from Citrus limon juice, we characterized flavonoids, limonoids and lipids, and we found that among the identified compounds, LEVs contain hesperidin and eriocitrin, two flavonoids with well‐recognized beneficial properties. 27 , 30 , 31 The great interest in their use as anti‐inflammatory agents is paralleled to studies aimed at encapsulating these natural compounds in lipid structures to increase their stability and availability. 43 , 44 , 45 Since EVs are naturally occurring nanoparticles, they may represent an advantage in transporting biomolecules to target cells.…”
Section: Discussionmentioning
confidence: 99%
“…LEVs possess a variety of flavonoids, such as eriocitrin, quercetin, vicenin-2, naringin, hesperidin and limonoids, like limonin. Most of these natural compounds exert beneficial roles, such as antiinflammatory, [26][27][28] anti-oxidant, 29,30 anti-cancer properties, [31][32][33][34] neuroprotective effects 35,36 and contrast obesity in mice. 37 The identification of flavonoids content in LEVs prompted us to investigate the role of LEVs in inflammatory models.…”
Section: Metabolomic Content Of Levsmentioning
confidence: 99%